Effects of an SEL Program in a Diverse Population of Low Achieving Secondary Education Students - Van De Sande, Marion C.; Fekkes, Minne; Diekstra, René F.; Gravesteijn, Carolien; Reis, Ria; Kocken, Paul L. (Frontiers in Education, 2022)
Adolescents' social-emotional skills are associated with positive outcomes in psychosocial health and success in education and work. In this study, we examined the effectiveness of Skills4Life, a Social Emotional Learning program for preparatory vocational secondary education aimed at enhancing self-awareness, social awareness, self-management, relationship skills, and responsible decision making. Low-achieving students with additional educational needs participated in a quasi-experimental study, with an intervention (N=465) and a control group (N=274). We assessed the outcomes on social-emotional skills and psychosocial health using self-report questionnaires at pre-test (T0), after finishing the basic module (T1), and after finishing the internship module (T2). Multi-level regression analyses indicated no overall effects on the outcomes at T1 and T2. After completing the entire program at T2, students from non-western backgrounds had significantly unfavorable lower scores on social awareness and relationship skills. Positive effects were found on self-management and preparation for internships in students taught by experienced professional trainers compared to students taught by regular classroom teachers at T2. Alterations in the socio-cultural approach of the Skills4Life program and teacher training are needed to support all students in developing the social-emotional skills that they need for success at school and the workplace.